The Problem Of Darfur Region In Sudan; A Study Of Social And Economic Effects (Journal of the College of Basic Education, 2025)
Darfur region problem is one of the most complicated issues in Africa and the world. Therefore, the roots of this crisis hits deeply in the racial and ethnic factions of the Sudanese society, along with the natural factors that influence the escalation of conflicts over economic resources. This led to a civil war in Darfur, which inflicted the country with huge human losses along with material losses.